Model Pembelajaran Scramble Menggunakan Media Wayang Pahlawan untuk Meningkatkan Hasil Belajar IPS Peserta Didik Kelas V-A SDN 1 Sabaru Palangka Raya - Rita Rahmaniati; Bulkani Bulkani; Fitri Pujianti (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to find out: (1) Student learning activities in IPS (Social Sciences) learning on the application of scramble learning model using puppet hero media (Puppet Heroes), and (2) Improvement of IPS learning outcomes after application of learning model of scramble using media of wayang heroes. Data collection using observation and test, while for data analysis technique using the analysis technique of classical and individual completeness. From the research result, it can be concluded that: (1) learners are more active in IPS learning on the application of scramble learning model by using puppet hero media, students play an active role, motivated, cooperate with increasing concentration and speed of thinking during learning process in cycle I. the observation of teacher activity on the learning process conducted by observer I and observer II during social science learning process (IPS) in cycle I average aspects of teacher activity is 3.63 with very good criteria and the average aspects of the activities of learners that is 3.37 with good criteria, and (2) There is an increase in learning outcomes of IPS learners after the application of the model of learning scramble using the media of wayang heroes. This is indicated by the results of learning seen through the average scores of classes in the first cycle is 80.21 with the criteria achieved and meet the KKM 70, reaching the percentage of learning mastery learners classically that is 100%, with 85% classical completeness.